The Effect of School Climate and Peer Attachment on the Self-Esteem of Underprivileged Adolescents - Hani 'Athiyya Rafi; Neti Hernawati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2025)
Underprivileged adolescents often face challenges that affect their self-esteem, such as limited family support, unstable socio-economic conditions, and educational pressures. Although Islamic boarding schools provide educational and social support, the dormitory environment also presents challenges, including bullying. This study aims to analyze the influence of school climate and peer attachment on the self-esteem of underprivileged adolescents. his quantitative research employed a survey method and involved 60 underprivileged students at the Fathan Mubiina Tahfidz Qur’an Islamic Boarding School, who were selected using purposive sampling. Data were analyzed using Pearson correlation and multiple linear regression analysis. The correlation test results showed that gender, school climate, and peer attachment are significantly related to the self-esteem of underprivileged adolescents. Furthermore, the multiple linear regression test results indicated that school climate and peer attachment have a significant positive effect on the self-esteem of underprivileged adolescents. Gender was also found to have a significant negative effect on self-esteem, with female adolescents having lower self-esteem compared to males. This study emphasizes the importance of creating a positive school climate and strengthening social relationships among peers to improve the self-esteem of underprivileged adolescents.